Analysis of Raw Material Rice Inventory Control Using the Economic Order Quantity and Reorder Point Methods - Octavianty, Ellyn; Ilmiyono, Agung Fajar; Adinugraha, Muhammad Rafli (The Es Accounting And Finance, 2025)
This research aims to analyze the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods for controlling rice raw material inventory at Kedai Bubur Ayam Tuangyu. The study employs a descriptive exploratory approach with a case study methodology, utilizing both primary and secondary quantitative data. Data analysis was conducted using non-statistical research techniques with the EOQ method. Through EOQ, a more economical order quantity of 570 kg per order was determined, with a purchasing frequency of 14 times per year. Additionally, a safety stock of 170 kg was established, and the reorder point was set at 192 kg. The implementation of EOQ in rice inventory control is highly feasible, as this method optimizes inventory management and reduces costs by IDR 1,658,144.